Phenotypes of peripheral CD4+ T helper cell subsets in pregnant women with HBeAg-negative chronic asymptomatic HBV carriers - Guofang Feng; Yu Sun; Shifen Wang; Yan Lv; Cuilin Yan; Cuilin Yan; Yimin Zhu; Yongsheng Zheng; Dawei Cui; Dawei Cui (Frontiers in Cellular and Infection Microbiology, 2023)
BackgroundChronic hepatitis B virus (HBV) infection is a major public health problem worldwide, and mother-to-child transmission is the key mode of HBV infection. CD4+ T helper (Th) cells play a critical role in the immune microenvironment of specific maternal tolerance to the foetus during pregnancy. However, the roles of Th cell subsets in pregnant women (PW) with chronic asymptomatic HBV carriers (ASCs) remain completely unclear. Here, we aimed to characterize CD4+ T-cell immunity in PW with hepatitis Be antigen (HBeAg)-negative chronic ASCs.MethodsHuman peripheral blood mononuclear cells (PBMCs) from PW without HBV infection or with chronic ASCs and healthy controls (HC) were isolated, and CD4+ Th cell subsets were detected by flow cytometry in addition to serum cytokines. Serological HBV markers, liver function and hormone levels of these individuals were also tested.ResultsThe frequencies of circulating T follicular helper (Tfh) type 2 (Tfh2) cells were significantly evaluated, but Tfh1 cell frequencies were notably decreased in PW compared to HC. Moreover, the frequencies of Th22 cells were only notably increased in PW with chronic ASCs in comparison with PW. Additionally, increased levels of serum IL-4 were positively correlated with Tfh2 cell frequencies in healthy PW. Interestingly, serum P4 levels were positively associated with the frequencies of circulating Tfh2 or Th2 cells but were negatively related to the frequencies of circulating Tfh17 or Th17 cells in healthy PW. Although there were some changes in the other CD4+ Th cell frequencies and cytokine levels or other references, significant differences were not found among HC, healthy PW, PW with HBeAg-negative chronic ASCs.ConclusionCD4+ Th cell subsets played a critical role in the immune microenvironment of PW, and these findings provided potential evidence for why PW with chronic ASCs did not receive antenatal antiviral prophylaxis.